The Analysis Study of Diagnosis and Surgical Management of Hemorrhoids: A Comprehensive Systematic Review - Jiwa Zhaqi Adiguna; Betti Merdiani Putri; Metti Herliani (The International Journal of Medical Science and Health Research, 2025)
Background: Although its precise prevalence is unknown, haemorrhoidal illness is a common reason for surgical consultation. Epidemiological studies are uncommon, and the numbers differ. According to a previous study, the global prevalence ranged from 3 to 30%. With about 3.3 million scheduled or emergency visits annually, it is regarded as the fourth most common gastrointestinal diagnosis in the US. The aim: The aim of this study to show about diagnosis and surgical management of hemorrhoids. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Despite more complicated postoperative effects that may drive patient refusal, surgical treatment is associated with higher effectiveness and is necessary for less than 20% of patients who arrive with haemorrhoidal illness. We have emphasised surgical management-related elements that can help the practitioner make treatment decisions.